Associations of physical activity levels and screen time with oral glucose tolerance test profiles in Singaporean women of reproductive age actively trying to conceive: the S‐PRESTO study. Issue 7 (7th April 2019) - Bernard, J. Y.; Ng, S.; Natarajan, P.; Loy, S. L.; Aris, I. M.; Tint, M. T.; Chong, Y.‐S.; Shek, L.; Chan, J.; Godfrey, K. M.; Khoo, C. M.; Leow, M. K.‐S.; et al.
Abstract: Aim: To examine the associations of physical activity and screen time, a proxy for sedentary behaviour, with fasting and post‐load glucose levels in Singaporean women enrolled in a multi‐ethnic Asian preconception study. Methods: Moderate and vigorous physical activity and screen time (television and other electronic devices) were self‐reported by women enrolled in the S‐PRESTO cohort. Fasting, 30‐min and 120‐min glucose levels before and during a 75‐g oral glucose tolerance test were measured. Associations of physical activity and screen time with glucose levels were analysed using multivariable linear marginal regression. Results: A total of 946 women aged 31.4±3.7 years were examined, of whom 72% were of Chinese, 15.5% were of Malay, 9.3% were of Indian and 3.2% were of mixed ethnicity. A total of 32% of women reported being active, 36% watched television ≥2 h/day and 26% used electronic devices ≥3 h/day. In adjusted models, vigorous, but not moderate, physical activity was associated with lower overall glucose levels, and was associated more strongly with post‐challenge than fasting glucose levels. Compared to women not engaging in vigorous physical activity, those engaging in physical activity ≥75 min/week had lower mean fasting [–0.14 (95% CI –0.28, –0.01) mmol/l], 30‐min [0.35 (95% CI –0.68, –0.02) mmol/l] and 120‐min [–0.53 (95% CI –0.16, –0.90) mmol/l] glucose levels (overall P value=0.05). We found no associations of screen time with glucose levels. Conclusions: Independently of the time spent in non‐vigorous physical activity and using screens, engaging in vigorous physical activity may be a modifiable factor to improve glucose regulation in women of Asian ethnicity who are attempting to conceive. What's new?: Physical inactivity and television time have been associated with insulin resistance and Type 2 diabetes in adults, and with gestational diabetes mellitus in pregnant women. In a preconception cohort study in Singapore in 1000 women trying to conceive, women engaging in ≥75 min/week of vigorous physical activity had lower fasting and post‐load glucose levels than inactive women. Device‐specific screen time was not associated with glucose levels. Engaging in vigorous physical activity may, independently of moderate physical activity and screen time, be a modifiable factor to improve glucose regulation in women of Asian ethnicity attempting to conceive.